Предмет: Математика,
автор: heYOhey
Найти z1 + z2, z1 – z2, z1 • z2, если z1 = 6 + 4i z2 = 3i
Ответы
Автор ответа:
0
z1 + z2 = 6 + 4i + 3i = 6 + 7i
z1 - z2 = 6 + 4i - 3i = 6 + i
z1 * z2 = (6 + 4i)*3i = 18i + 12i^2 = -12 + 18i
z1 - z2 = 6 + 4i - 3i = 6 + i
z1 * z2 = (6 + 4i)*3i = 18i + 12i^2 = -12 + 18i
Похожие вопросы
Предмет: Информатика,
автор: philolosharik
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: yashinhalimov
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Екатеринка20020305